The Political Communication Forms Running on Caliph Ali Ibn Abi Thalib’s Government - Khairul Hakim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to find out the political communication forms that running on caliph Ali Ibn Abi Thalib’s government. This study use qualitative method. The result shows The political agitation of the Caliph Ali in the content of his sermons and letters by stimulating and arousing the public's emotions, to be willing to make great sacrifices for the immediate goal and be willing to sacrifice the soul to realize a political ideal, when the Caliph Ali and the Shiffin war and the Jamal war. The agitation carried out by Caliph Ali did not have a negative connotation which was inciting or threatening, but was to excite or encourage his followers to win. Not agitation by making contradictions in society. While the political propaganda of the Caliph Ali was not the same as what Hitler did in World War II by making lies in spreading Nazi ideology to expand his influence and power. When Caliph Ali made a letter to Mu'awiah and the rebels at that time was not to expand power but to restore the state order based on the Qura’an and Hadith.